Momentify: Photo Management System with Integration of Facial Recognition - SAIPUDIN, LUTFIR RAHMAN; KASIM, SHAHREEN (Applied Information Technology And Computer Science, 2025)
The increasing complexity of managing event photography highlights the limitations of traditional platforms that rely heavily on manual operations and lack intelligent search capabilities. This study aims to develop Momentify, a scalable web-based application integrated with AWS Rekognition to enhance photo organization through facial recognition and role-based access control. The research adopted the Agile methodology and involved structured workflows including system analysis, interface design, functional and security testing, and user acceptance evaluation. Key findings reveal high user satisfaction in terms of navigation, face search accuracy, and photo upload efficiency, particularly among Event Managers and Photographers. Results affirm the system’s ability to streamline user roles, automate facial identification, and improve the user experience for large-scale events. The study concludes that Momentify is a viable solution to current photo management inefficiencies and recommends future work in expanding reporting tools and UI customization.